Is it because of I'm famous, success or rich: why social media influencer become a victim of cyberbullying on social media? - Ab Rashid, Faridah Hanem; Omar, Siti Zobidah; Bolong, Jusang; Wan Abas, Wan Anita (Human Resource Management Academic Research Society, 2022)
Social media influencers have significant followers, which includes both enthusiastic engaged people who appreciate their opinions and detractors. While they benefit from the chances to become brand endorsers as a result of their influences, they are also potential victims of cyberbullying. Cyberbullying is not a new phenomenon; it predates the social networking era. Therefore, this study examined on why social media influencers become a victim of cyberbullying on social media adopted by the past researcher. A comprehensive online questionnaire was used to assess the type of cyberbullying which has four dimensions such as harassment, flaming, dissing, and trust. The respondents for this study were generally 50 influencers in Malaysia. Data were analyzed using SmartPLS 3. The findings showed that all the hypotheses tested were supported and it concludes that the social media influencer in Malaysia was a victim of cyberbullying on social media. As for the recommendation, the results obtained give insight and perspective whereby the action needs to be taken promptly by authorities in Malaysia in overcoming this issue before it is too late.